2010
DOI: 10.1111/j.1462-5822.2010.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin C-terminal hydrolase UCH-L1 promotes bacterial invasion by altering the dynamics of the actin cytoskeleton

Abstract: SummaryInvasion of eukaryotic target cells by pathogenic bacteria requires extensive remodelling of the membrane and actin cytoskeleton. Here we show that the remodelling process is regulated by the ubiquitin C-terminal hydrolase UCH-L1 that promotes the invasion of epithelial cells by Listeria monocytogenes and Salmonella enterica. Knockdown of UCH-L1 reduced the uptake of both bacteria, while expression of the catalytically active enzyme promoted efficient internalization in the UCH-L1-negative HeLa cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Recent studies demonstrate that inhibition of the expression of UCH-L1 reduces the tumorigenic phenotype of transformed cells, including virus-transformed B-lymphocytes (Bheda et al, 2009a; Kim et al, 2008; Rolen et al, 2008). UCH-L1 also associates with cytoskeletal components, including microtubules (Bheda et al, 2010; Kabuta et al, 2008) and actin filaments (Basseres et al, 2010), and it physically associates with mitotic spindles (Bheda et al, 2010), which suggests a potential role in the regulation of mitosis. Furthermore, oncogenic transcription factors, such as B-Myb and β-catenin/TCF, up-regulate the expression of the uch-l1 gene (Bheda et al, 2009b; Long et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that inhibition of the expression of UCH-L1 reduces the tumorigenic phenotype of transformed cells, including virus-transformed B-lymphocytes (Bheda et al, 2009a; Kim et al, 2008; Rolen et al, 2008). UCH-L1 also associates with cytoskeletal components, including microtubules (Bheda et al, 2010; Kabuta et al, 2008) and actin filaments (Basseres et al, 2010), and it physically associates with mitotic spindles (Bheda et al, 2010), which suggests a potential role in the regulation of mitosis. Furthermore, oncogenic transcription factors, such as B-Myb and β-catenin/TCF, up-regulate the expression of the uch-l1 gene (Bheda et al, 2009b; Long et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that interactions of IQGAP1 with Salmonella-activated Rac1 and Cdc42 maintain them in their active form [32,33]. Another host factor that contributes to bacterial invasion by altering the dynamics of the actin cytoskeleton is the ubiquitin C-terminal hydrolase UCH-L1 [34]. Since SopA, SopB, and SopE are substrates of the ubiquitin proteasome system, it has been suggested that UCH-L1, acting as a deubiquitinating enzyme, could play a role in controlling the half-life of these effectors and/or the activity of small GTPases of the Rho subfamily.…”
Section: Actin Cytoskeleton and Invasionmentioning
confidence: 99%
“…Particularly, UCHL3 has been found to be significantly downregulated during infection with virulent strain, as compared to control cells, or cells infected with virulence plasmid-cured strain. A close homologue of this DUB, UCHL1, has been already shown to be involved in bacterial entry of Listeria monocytogenes and Salmonella enterica Typhimurium [80], therefore our current finding might be physiologically very interesting and warrants further study.…”
Section: Dubs In Bacterial Infectionsmentioning
confidence: 72%
“…A human ubiquitin C-terminal hydrolase UCHL1 has been shown to promote Listeria monocytogenes and Salmonella enterica epithelial cell invasion and induce spontaneous formation of actin stress fibers, regulating early events in receptor signaling [80]. In particular, UCHL1 controls early membrane-associated pathways related to the L. monocytogenes entry into the host cell, such as activation of downstream ERK1/2- and AKT-dependent signaling in response to the Hepatocyte Growth Factor (HGF).…”
Section: Dubs In Bacterial Infectionsmentioning
confidence: 99%